Measuring Changes in Creativity Thinking of Hydrocarbon Concepts in Students Taught with Hyperdocs Worksheet Modeling - Laliyo, Lukman A.R; Lamatenggo, Widya Lestari; Tangio, Julhim S; Katili, Yeyen Apriani (Universitas Negeri Gorontalo, 2024)
This research was conducted to determine the changes in conceptual thinking creativity in hydrocarbons among students who were taught by using the Hyperdocs Worksheet at SMA Negeri 7 Gorontalo on hydrocarbon material. The method used in this research was a quasi-experiment with a non-equivalent control group design. The research samples consisted of students from class XI Merdeka 1 as the experiment group and XI Merdeka 2 as a control group at SMA Negeri 7 Gorontalo, selected using purposive sampling. The research from the creative thinking ability test were statitically processed, including prerequisite test consisting of normality and homogeneity tests. The result showed normal distribution and homogeneity. The average pre-test score for the experimental class was 31% and the post-test score was 82%, while the control class had an average pre-test score of 28% and a the post-test score 60%. Furthermore, based on the hypothesis testing using a t-test at a significance level of Î± = 0.05, a tcount was 9.25 with a ttable of 1.671. This indicates that tcount > ttable, leading to the conclusion that H0 is rejected and H1 is confirmed, indicating a change in conceptual thinking creativity hydrocarbons among students taught using by modeling Hyperdocs Worksheets modeling. The results of the N-Gain test showed that the average N-Gain score for the experiment class was 0.73 and that for the control class, it was 0.43, indicating a high N-Gain score in the experimental class. Therefore, using Hyperdocs Worksheets modeling effectively enhances students' creativity in thinking about hydrocarbon concepts.